2013
DOI: 10.1111/1471-0307.12096
|View full text |Cite
|
Sign up to set email alerts
|

Water utilisation, energy utilisation and waste water management in the dairy industry: A review

Abstract: Energy consumption, water utilisation and waste production are now important environmental issues. However, compilations of data are not readily available, making it difficult for companies to assess how they are performing. This review aims to summarise the data that are available, including some benchmarking values. Also discussed are techniques for reducing water and energy consumption and waste production, tools for monitoring this and assistance that is available to improve efficiency ratios and reduce co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 10 publications
1
58
0
3
Order By: Relevance
“…Many milk-processing plants use this ratio to track their overall consumption. The ratios are within the European range of 0.2-11 l/kg reported by Daufin et al (2001) and the Australian range of 0.07-2.9 l/kg reported by UNEP (2004) and above the range of 0.5-0.78 reported for cheese production in UK by Milani, F.X., Nutter, D. & Thoma, G. (2011) (Rad and Lewis, 2014).…”
Section: Water Use In the Milk-processing Plantssupporting
confidence: 82%
See 2 more Smart Citations
“…Many milk-processing plants use this ratio to track their overall consumption. The ratios are within the European range of 0.2-11 l/kg reported by Daufin et al (2001) and the Australian range of 0.07-2.9 l/kg reported by UNEP (2004) and above the range of 0.5-0.78 reported for cheese production in UK by Milani, F.X., Nutter, D. & Thoma, G. (2011) (Rad and Lewis, 2014).…”
Section: Water Use In the Milk-processing Plantssupporting
confidence: 82%
“…A detailed mapping of water use is generally agreed as a precondition for a comprehensive reduction of water use (Perry, C., 2011;Mavrov, V. & Belieres, E., 2000;Rad and Lewis, 2014). In the present project, the methodologies applied were sufficiently detailed to lead to the identification of scenarios using the 6Rs and "water-fit-for-purpose" approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The value of the Pearson correlation coefficient for the total energy consumption (EC) and obtained purity of exchanger plates (JM) was r = 0.01, what indicates a lack of relationship between the variables which were analyzed. The obtained results also demonstrated that the main reason for high energy consumption in the process of cleaning of the dairy installations, is high temperature of cleaning agents in the range of 65 − 85 °C (Rad and Lewis, 2014;Ramirez et al, 2006), although according to presented results, this factor does not improve the efficiency of removal of milk residues from the exchanger plates (programs 3, 4, 11). Similar results were obtained by Diakun et al (2012) and Wojdalski et al (2013).…”
Section: Analysis Of the Efficiency Of Cleaning In Relation To Total mentioning
confidence: 65%
“…The basic ones include technology of food processing, technical equipment, degree of automation and mechanization of production operations, thermophysical properties of materials, requirements for products, magnitude and structure of production and its organization (Bunse et al, 2011;Marchini et al, 2014;2015; and related with those the operations of cleaning and disinfection of machines and production equipment. Some reports indicate that the cleaning processes in food industry are energy-intensive processes and that in the food industry they require even about 13.5 -14% of the total process energy consumption (Neryng et al, 1990;Pawełas, 2010;Rad and Lewis, 2014). This consumption primarily results from the operation conditions of the CIP cleaning station, type and size of the objects subjected to cleaning and the choice of cleaning agents (Piepiórka-Stepuk et al, 2016;Ramirez et al, 2006;Wojdalski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%